Let total amount = T.
A would have got T * a. After A takes his share, there would be T (1 - a) left
B would have got T (1 - a) * b
C would have got T (1 - a)(1 - b) * c
D would have got T (1 - a) (1 - b) (1 - c)
D gets a % less than what A gets, or, T *a (1 - a) = T(1 - a) (1 - b) (1 - c), or
a = (1 - b)(1 - c) -------- Eqn 1
B and C get the same amounts, or (1 - a) * b = (1 - a) * (1 - b) * c, or b = (1 - b) c, or, b = c - cb, or
b = + 1 ------------ Eqn 2
b = 2a -----------------Eqn 3
Substituting, eqn 2 in and 3 in eqn 1, we get
Or, c = 2 -2c, or c =
b = , a =
a gets 20% of the loot, b gets 40% of the remaining 80%, or 32% of the loot. C gets 66.6% of 48%, or 32% of the overall loot. And d gets the final 16% of the overall amount (20% lesser than A's share).
Now, to the questions,
All features of the online course, including the classes, discussion board, quizes and more, on a mobile platform.
Download videos onto your mobile so you can learn on the fly, even when the network gets choppy!